Figure it out! drawing essential poses the beginner's guide to the natural-looking figure - Hart, Christopher 1957- (New York Sixth & Spring Books, 2016)
"Bestselling how-to-draw author Christopher Hart helps artists fine-tune their skills with the fundamentals of drawing natural-looking figures. Eschewing the esoteric "art poses" and wooden mannequins commonly found in art books, he portrays everyday, real-life gestures on human-looking foundation figures: standing, sitting, kneeling, and reclining, with arms folded, ankles crossed, hands on hips, and more, all shown from various angles. Hart also explores deeper concepts such as perspective, illusion of depth, casting shadows, and foreshortening, and provides step-by-step tutorials that take artists through complete, naturally posed figure drawings from start to finish"--Provided by publisher.
Includes index.
Keywords: Figure drawing -- Technique; ART / Techniques / Drawing; ART / Subjects & Themes / Human Figure; ART / Techniques / General